Tipsy Testimonies: The Effect of Alcohol Intoxication Status, Crime Role and Juror Characteristics on Mock Jury Decision‐Making - Martin, Erica; van Golde, Celine; Monds, Lauren A. (Applied cognitive psychology, 2024)
ABSTRACT Victims and witnesses are regularly intoxicated with alcohol during crimes and jurors must evaluate their testimony when making decisions. The current study employed a 2 (crime role: victim, witness) × 4 (victim/witness intoxication status: sober, low, moderate, severe) between‐subjects design. Juror characteristics (e.g., alcohol expectancies, personal alcohol consumption, alcohol‐related work experience, demographic factors) were also explored as predictors of mock jury decision‐making. Participants (N = 181) read a trial transcript and completed a survey assessing trial‐related judgements, demographics, and expectations about and experiences with alcohol. Lower victim/witness intoxication was associated with higher credibility ratings, lower cognitive impairment ratings, and more convictions. Crime role did not impact dependent variables and juror characteristics had a limited influence: only alcohol‐related work experience and the perceived gender of the victim/witness predicted a minority of decision types. The current study asserts the need for evidence‐based jury education about alcohol and eyewitness memory with a focus on delivery via familiar metrics.